2006
DOI: 10.1271/bbb.70.782
|View full text |Cite
|
Sign up to set email alerts
|

The Region in a Subunit of theAspergillusCCAAT-Binding Protein Similar to the HAP4p-Recruiting Domain ofSaccharomyces cerevisiaeHap5p Is Not Essential for Transcriptional Enhancement

Abstract: The CCAAT-binding complex in Aspergillus species, known as the Hap complex, consists of at least three subunits, HapB, HapC, and HapE. Each Hap subunit contains an evolutionarily conserved core domain. In this study, a series of the truncated gene, which encodes the HapE subunit of Aspergillus oryzae, was constructed to survey the regions essential for the transcriptional enhancement of fungal genes. It was revealed that the non-conserved regions and the conserved region similar to the Hap4p recruiting domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In contrast, domain A is only conserved among fungal HapE orthologs and has been shown to be required for the recruitment of Hap4p in S. cerevisiae . Recently, Tanoue et al (2006) reported that only the B‐domain is required for CBC‐mediated transcriptional activation in A. nidulans . Here, we found that deletion of the non‐conserved N‐terminal region and the A‐domain phenocopies hapX deletion, that is, wild type‐like growth during +Fe conditions, but decreased growth rate, reduced TAFC production, and increased accumulation of FC and PpIX during −Fe conditions (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, domain A is only conserved among fungal HapE orthologs and has been shown to be required for the recruitment of Hap4p in S. cerevisiae . Recently, Tanoue et al (2006) reported that only the B‐domain is required for CBC‐mediated transcriptional activation in A. nidulans . Here, we found that deletion of the non‐conserved N‐terminal region and the A‐domain phenocopies hapX deletion, that is, wild type‐like growth during +Fe conditions, but decreased growth rate, reduced TAFC production, and increased accumulation of FC and PpIX during −Fe conditions (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…( B ) Growth rates and production of TAFC, FC and PpIX after growth for 48 h during+Fe and −Fe conditions. For induction of amylase promoter‐driven genes (Tanoue et al , 2006), strains were grown in medium containing starch as the sole carbon source. During +Fe conditions, production of TAFC, FC and PpIX was wild type‐like in all strains (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The complex is a transcription factor that specifically recognizes the regulatory CCAAT element found in the forward or reverse orientation in promoter regions of numerous eukaryotic genes [70]. The hapE gene contains four exons and the mutation is situated in the fourth exon, in the evolutionary conserved core domain [62], [63], [71], suggesting that P88 is an important amino acid for the function of the protein. Moreover, in the human NF-YC (the mammalian HapE homologue) deletion of residues 43–45 (homologous to A. fumigatus residues 87–89), are deleterious for DNA binding [72], indicating that P88 is needed for the Hap-complex to bind the regulatory CCAAT element and initiate transcription.…”
Section: Discussionmentioning
confidence: 99%